2020
DOI: 10.1088/1755-1315/448/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Filariasis Vulnerability Zonation Based on Environmental and Behavioural Aspects in Pekalongan City, Indonesia

Abstract: Pekalongan City is a filariasis endemic area in Central Java, Indonesia with Mf-rate >1%. It had held Mass Drug Administration (MDA) in 2011-2015. The evaluation result recommended it to re-hold MDA. This study aimed to compose filariasis vulnerability zonation based on environmental and behavioural aspects in Pekalongan City. The observed environmental aspects were the location of shrubs, cattle pen and tidal flood. The surveyed behavioural aspects were applicating mosquito repellent and hanging clothes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The presence of cattle pens will attract more mosquitoes to come. It causes people who live in cattle pens surrounding have a higher risk to be bitten by mosquitoes and infected LF (Siwiendrayanti, Pawenang, Indarjo, et al, 2020). 3 patients were in a mosquito flight radius from a cattle pen, and 7 patients were in a mosquito flight radius from both unmaintained bushes and a cattle pen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of cattle pens will attract more mosquitoes to come. It causes people who live in cattle pens surrounding have a higher risk to be bitten by mosquitoes and infected LF (Siwiendrayanti, Pawenang, Indarjo, et al, 2020). 3 patients were in a mosquito flight radius from a cattle pen, and 7 patients were in a mosquito flight radius from both unmaintained bushes and a cattle pen.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of infective larval infection in the anopheles vector varies according to mosquito species and local conditions but is often around 0.1-5% for Adult mosquitoes need a certain site, called a resting place, to rest after and before biting for a blood meal. Previous studies found cattle pens, unmaintained bushes, and maintained bushes as important outdoor resting places for adult mosquitoes (Siwiendrayanti, Pawenang and Indarjo, 2017;Khikmah and Pawenang, 2018;Siwiendrayanti, Pawenang, Indarjo, et al, 2020). It is needed to identify what kind of resting place contributes more to LF distribution in rural areas in Brebes Regency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurjazuli's research in Pekalongan City in 2012 on filariasis prevention behavior by using a mosquito net while sleeping, the presence of house ventilation with mosquito netting, using mosquito repellent, not hanging clothes, and environmental management [12] [13]. Risk factors for vector presence in the house, environmental improvement , the existence of ditches, ditches, puddles, predators, livestock, bushes, water plants, rice fields and swamps [14] [15].…”
Section: Introductionmentioning
confidence: 99%
“…The age of school children is also the object of the prevention of filariasis / POMP which is carried out jointly by the Pekalongan City Health Office [15]. Implementation of the pre-Transmission Assessment Survey (TAS) and TAS-1 was carried out by the City of Pekalongan to complete the POMP during 5 rounds (5 times over a period of 5 years) in 2015; or declared not passing TAS-1, the POMP is re-carried out for 2 rounds (2 times within 2 years) which was carried out the last in 2018 [16].…”
Section: Introductionmentioning
confidence: 99%